Antifeedant Potency of some Plants Produce against Defoliating Pest of Poplar, Clostera cupreata - Ahmad, Mukhtar; Dayal, Rameshwar; Mishra, R. K; Dobhal, P. C (Indian Forester, 1997)
Natural forest products have long been known to possess insecticidal, insect growth regulating and antifeedant properties. Doring present studies extractives of some forest produce including acetone and alcohol extracts of bark and roots of Dalbergia stipulacea, leaves of Eucalyptus hybrid and Adina conlifolia, ursolic acid and bryonolic acid were evaluated as insect antifeedant against poplar defoliator Clostera eupreata (Lepidoptera : Notodontidae). Ursolic acid (separated from Euealyptru hybridleaves extract) has shown maximum antifeedant activity and gave over 92 per cent protection of poplar leaves from its pest. It was followed by alcohol and acetone extracts of Eucalyptru hybrid leaves, bryonolic acid, acetone extract of D. stipulacea bark, alcohol extract of A. cordifolia leaves etc. Solvents play important role in extracting active ingredient of specific nature as acetone extracts of D.stipulacea were found more effective than their alcohol extracts while solvents (acetone and alcohol) did not sbow any antifeedant activity on their own.